How service quality in hospitals varies based on hospital ownership and demographics: a study on Turkish patients living urban areas. (19th May 2022) - Yarimoglu, Emel; Ataman, Gorkem
Abstract : Recently, measuring service quality in hospitals has become crucial topic, since the increasing importance of healthcare sector. The aim of the study was to show the differences in patients' service quality perceptions based on hospital ownership and demographics in Turkey. Service quality was measured by SERVPERF scale, and the survey was conducted with 715 patients, chosen by convenience sampling in Izmir City, Turkey, using face-to-face survey technique. Between-subject factorial ANOVA designs (2*2 and 2*3) were used in data analysis. In findings, main effects for hospital ownership were found to be significant in all models. It showed that service quality in private hospitals was perceived higher than public hospitals. However, main effects for demographics were not significant. The interaction effects between hospital ownership and only three demographics (age, marital status, and income) were found to be significant. These showed that younger patients perceived service quality higher in private hospitals, while older patients perceived it lower. Single patients perceived service quality higher in private hospitals than married patients, while the opposite was observed for public hospitals. The medium or high-income level patients perceived service quality higher in private hospitals, but the opposite was obtained for public hospitals.